Enhancing Children's Creativity Through Art-Based Learning in Early Childhood: A Strategy to Stimulate Gross and Fine Motor Development - Hasanah, Uswatul; Kamila, Fi’isatil; Wulandari, Rika; Caesar Rahmawati Khoirina, Riila (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Early childhood is a critical period for fostering creativity and developing motor and socio-emotional skills. Integrating art into early childhood education has the potential to stimulate these aspects in a holistic manner. However, there is still limited research on how art-based learning strategies affect children's overall development, especially in the context of Indonesian early childhood institutions. Aims and scope of paper: This study aims to explore the effectiveness of implementing art as an integrated learning strategy at RA Bakti Telang. It focuses on examining the impact of art activities on the development of children’s creativity, gross and fine motor skills, and socio-emotional abilities. Methods: A qualitative case study approach was employed. Data were collected through classroom observations, in-depth interviews with teachers and parents, and documentation of art activities conducted at the school. Thematic analysis was used to interpret the findings. Results: The study found that art activities such as traditional dance, hadroh (Islamic percussion performance), and coloring significantly enhanced children's creativity and positively stimulated both gross and fine motor development. Dance activities improved body coordination and balance, while coloring refined fine motor control through the use of writing tools. Additionally, participation in group art projects fostered social skills such as cooperation and empathy. A key challenge identified was the limited involvement of parents, particularly fathers, in supporting these activities. Contribution: This study contributes to the development of a more inclusive and adaptive model of art education for early childhood settings. It offers practical recommendations for increasing family engagement and provides guidance for other early childhood education institutions seeking to implement more effective and comprehensive art-based programs.